Via Vallen’s selection process as the local singer for Lead the Way film’s official soundtrack - Miranda Shafira Alamsyah; Hanny Hafiar; Ade Kadarisman (Universitas Padjadjaran, 2023)
Background: Using celebrity endorsement to represent a brand can provide various advantages. However, if in selecting a celebrity endorser, the brand has not carried out the selection process correctly and precisely; then the brand can be threatened to face various risks due to celebrity endorsement tactics. Walt Disney Studios Indonesia experienced this in selecting Via Vallen as the singer of the localization song for the “Lead the Way” Official soundtrack. Purpose: This study aims to describe and analyze the selection process of Via Vallen. Methods: This study uses a qualitative approach with a descriptive type of research. Data collection techniques used are observation, interviews, and literature study. The data validation technique is done by using source triangulation. Results: The results showed that in the selection process of Via Vallen, the Walt Disney Studios Indonesia had carried out a series of selection stages as follows: market research, presentation, discussion to narrowing of candidates, meeting to final negotiations, and ending it with the signing of the contract. However, Walt Disney Studios Indonesia has not yet done the steps of contacting a PR agency to create an MPR campaign and proposing the use of celebrity endorsement tactics by the PR agency. Implications: Based on this research, it can be concluded that Walt Disney Studios Indonesia and similar companies could be more careful in choosing celebrity endorsers to represent brands to avoid disadvantages that could harm the brand. In addition, to strengthen this model, quantitative research can be carried out to see whether this model has a relationship with the success of choosing a celebrity endorser that can benefit a company.